Empirical search and characterization of contemporaneity using breaks and regime switching - Delbianco, Fernando Andrés (2017)
This paper describes a technique to determine the contemporaneity of two economic events. It is also possible to determine some characteristics of the contemporaneity, as a descriptive stage previous to causality analysis and model estimations. As an illustration, a case of contemporaneity between news and volatility in financial markets is shown. The main result of the exercise is a Laffer curve relationship between corruption and volatility given news.